Kontribusi Koordinasi Mata Tangan, Kelentukan Pergelangan Tangan dan Keseimbangan Terhadap Kemampuan Untuk Servis Panjang dalam Permainan Bulutangkis Pada Siswa - Herman, Herman (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2019)
This study aims to determine the contribution of hand-eye coordination with long serviceability, the contribution of wrist flexion with long serviceability, contribution of balance with serviceability and contribution of hand-eye coordination, wrist flexion and balance to long service in badminton play in MAN 2 Kota students Makassar. The research method or method used in this study is a "descriptive" research method with regression techniques. Data for this study were collected through hand-eye coordination tests, wrist flexion, and balance tests. After all the assessment data have been collected, then to test the hypotheses proposed in this study, and the data is compiled and processed through SPSS version 21, the significant level is α = 0.05 (95%). The results obtained are significant contributions together in coordination. eye-hand, wrist flexion and balance to long service abilities in badminton games at MAN 2 Makassar City students.